Using Augmented Reality for Geometry Learning: Indonesian Elementary School Teachers' Experiences - Dede Nurhidayah; Asep Nuryadin; Karlimah Karlimah; Dindin Abdul Muiz Lidinillah; Ika Fitri Apriani; Irni Rachmawati Putri; Lilis Susilawati; Ginna Islamiati (Pascasarjana Universitas Negeri Malang (UM), 2023)
This study aims to discover Indonesian elementary school teachers' experiences (n = 257) of using Augmented Reality (AR) for learning, especially related to one of the topics in mathematics learning, namely, geometry. AR is considered to be an alternative instructional media that can be utilized for teaching geometry, including the topic of three-dimensional shapes. A questionnaire consisting of both close-ended and open-ended questions was used to collect data in this study. This study has successfully revealed teachers' use of digital instructional media during the COVID-19 pandemic, their familiarity with AR, frequency of AR use for geometry learning, and challenges in using it. DOI: 10.17977/jps.v11i12023p001